Peace agreements between State-Guerrillas in Colombia, 1982-2016 - Villarraga- Sarmiento, Álvaro (Universidad Pedagógica y Tecnológica de Colombia, 2016)
In Colombia a global and simultaneous agreement was not reached between the national Governments and the different guerrillas that have led an armed uprising that surpassed half a century. The model of negotiation has been the estalishment of bilateral tables with each of the guerrillas and even alsowith dissident guerrilla factions and with urban and rural peasant militias. In spite of the prolongation of the internal irregular war, these definitive pacts of peace have been made progressively, although have also been interspersed with episodes of conversation tables with several of the guerrillas with failed results